Mandatory versus voluntary Continuing Professional Education: perspectives from the nursing profession - Chan, Man Wai, Sarah (2017)
Continuing Professional Education (CPE) is constantly evolving and is now mandatory in some professions in many countries. In Hong Kong, CPE for nursing profession remains voluntary. This research seeks to gather the perceptions, opinions and voices of nurse practitioners, college leaders and academic experts in Hong Kong if CPE is changed from a voluntary basis to a mandatory regime with the focus on analyzing different aspects of CPE. A literature review was carried out in order to distill the views of international scholars and practitioners, together with a review of policies pertaining to continuing professional development (CPD) and CPE. Furthermore, theoretical and practical implications were discussed, and suggestions for future researchers were made. In order to answer the research questions, a phenomenological qualitative study was conducted on the subject topic. Regarding the conceptual framework, the adult learning theory supplemented by motivation theories were scrutinized and analyzed while discussing the application of CPE.